The role of youth engagement in positive youth development and social justice youth development for high-risk, marginalised youth. Issue 3 (2nd July 2016) - Iwasaki, Yoshitaka
Abstract: This article describes reflective experiences documented by our youth leaders and community agency partners ( n = 7 & 12, respectively) who have involved in our multi-year community-based research project. Overall, meaningful youth engagement facilitated by youth leadership was highlighted as a key mechanism for positive youth development (PYD) and social justice youth development (SJYD). First, the key PYD-related concepts identified include the following: (1) strengths-based empowering approach to youth engagement, (2) capacity building and positive outcomes for youth and youth-serving agencies and (3) youth-oriented, collaborative research processes that enable the promotion of these positive outcomes (e.g. honouring youth voice: 'bottom-up process for youth by youth'). Second, the key SJYD-related concepts identified were as follows: (a) activating the voice of youth for social/system change, and (b) advancing research into action – knowledge translation and practical application. The contributions of our youth leaders to youth engagement were shown to be vital to promoting PYD and SJYD.